2016
DOI: 10.1182/blood.v128.22.4770.4770
|View full text |Cite
|
Sign up to set email alerts
|

General Adaptive Functioning in Survivors of Childhood Acute Lymphoblastic Leukemia

Abstract: Continuous advancement in treatment strategies for childhood acute lymphoblastic leukemia (ALL) have improved survival rates markedly over the past decades. The overall 5-year survival rate is now approaches 90% for survivors treated with contemporary therapies that include central nervous system (CNS)-directed chemotherapy and intensified systemic chemotherapy. Late effects however, including neurocognitive deficits and osteonecrosis may present lifelong consequences for survivors. Children's Oncology Group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found that females had greater attention problems than males over time, suggesting greater susceptibility to neurocognitive weaknesses. Results from studies examining sex differences in neurocognitive functioning in survivors of ALL have been inconsistent (Baran et al, 2016;Brinkman et al, 2013;Espy et al, 2001;Halsey et al, 2011;Jacola et al, 2016b;Jansen et al, 2008). Further research will be needed to disentangle the effects of sex and medical complications.…”
Section: Discussionmentioning
confidence: 99%
“…We found that females had greater attention problems than males over time, suggesting greater susceptibility to neurocognitive weaknesses. Results from studies examining sex differences in neurocognitive functioning in survivors of ALL have been inconsistent (Baran et al, 2016;Brinkman et al, 2013;Espy et al, 2001;Halsey et al, 2011;Jacola et al, 2016b;Jansen et al, 2008). Further research will be needed to disentangle the effects of sex and medical complications.…”
Section: Discussionmentioning
confidence: 99%